Evaluasi Aplikasi Depok Single Window (DSW) dalam Mendukung Konsep Smart City di Dinas Komunikasi dan Informatika Kota Depok - Mary Ismowati; Funny Indri Widyastuti (Faculty of Social Science, Universitas Negeri Padang, 2023)
The Depok Single Window (DSW) application is a media portal in the form of e-Government which was initiated by the Depok City Communication and Information Department to make it easier for people to get services and can also support the smart city concept. The background to this research is that many people in Depok City are not aware of the existence of the Depok Single Window (DSW) application, and there are still several services provided by each OPD that have not been integrated, as well as many complaints from the public. There was a decrease in the level of use of the Depok Single Window (DSW) application. The purpose of this research is to determine the evaluation of the Depok Single Window (DSW) application in supporting the Smart City Concept in the Depok City Communication and Information Department. The method used is a descriptive qualitative method by conducting interviews, observation and documentation. There are 6 (six) dimensions consisting of effectiveness, efficiency, adequacy, alignment, responsiveness and accuracy. The data source used is primary data obtained directly from informants and observations. Secondary data comes from existing data from the Depok City Communication and Information Office as well as documents. The results of the research show that the evaluation of the Depok Single Window (DSW) application has been carried out sufficiently to support the smart city concept in the Depok City Communication and Information Department, which is a form of smart government. However, implementation is still not optimal. There are still quite a lot of people in Depok City who don't know about it and there are still several obstacles experienced by people in using it. It was concluded that the evaluation of the Depok Single Window (DSW) application had been carried out but had not been carried out optimally.